2019
DOI: 10.1029/2019gl082126
|View full text |Cite
|
Sign up to set email alerts
|

Interplanetary Shock Parameters Near Jupiter's Orbit

Abstract: Fast interplanetary shocks occurrence, their parameters, and drivers near Jupiter's orbit are determined in this paper. It was found that 70% of the fast shocks are forward (FS) and 30% are reverse (RS). Interplanetary coronal mass ejection‐driven FS occur more frequently in all solar cycle phases except in the declining phase, when corotating interaction region‐driven shocks predominate. Most of the shocks were quasi‐perpendicularly (65° to 70°) propagating relative to the ambient interplanetary magnetic fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
(131 reference statements)
0
4
0
Order By: Relevance
“…Interplanetary (IP) shocks are solar wind structures commonly observed in the heliosphere (Echer, 2019; Harada et al., 2017; Mihalov et al., 1987; Richardson & Wang, 2005; Winslow et al., 2015). IP shocks arise when the ratio of the relative speed (between the ambient solar wind and the shock itself) to the local magnetosonic speed, defined as the magnetosonic Mach number, is greater than 1 (Jeffrey & Taniuti, 1964; Priest, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Interplanetary (IP) shocks are solar wind structures commonly observed in the heliosphere (Echer, 2019; Harada et al., 2017; Mihalov et al., 1987; Richardson & Wang, 2005; Winslow et al., 2015). IP shocks arise when the ratio of the relative speed (between the ambient solar wind and the shock itself) to the local magnetosonic speed, defined as the magnetosonic Mach number, is greater than 1 (Jeffrey & Taniuti, 1964; Priest, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…These results can be compared with the radial variations of shock parameters in the outer heliosphere, beyond ∼1.0 au from the Sun. The shock occurrence is found to peak at ∼5.0 au (e.g., Hoang et al 1995;González-Esparza et al 1998;Richardson & Wang 2005;Neugebauer 2013;Echer 2019), beyond which it decreases linearly (Hajra 2021). In addition, Hajra (2021) reported that the radial variation of the shock M ms between ∼1.0 and ∼15.0 au is slower and less correlated to r h .…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The interplanetary fast shocks were identified on mSWim data using the characteristics described by Echer et al 2010 [13] and Echer 2019 [20]. Those shocks are described as follows:…”
Section: Interplanetary Fast Shocksmentioning
confidence: 99%